(untitled) - Moyer, R. Charles (Minneapolis/St. Paul, 1995)
CONTEMPORARY FINANCIAL MANAGEMENT introduces the principles you need to know to maximize shareholder wealth and effectively manage cash flow. You'll explore the international aspects of financial management, examine the ethical behavior of managers, and study the increased impact of the Internet in today's business practice. Expanded coverage of topics such as financial forecasting and risk management highlights areas of growing financial importance. Financial Challenges, icons, integrative cases, and other learning features highlight critical concepts and provide practice to help you master the concepts discussed. Excel templates offer additional practice in using technology to achieve financial management objectives. Thomson ONE Business School Edition gives you the same financial analysis tool that Wall Street professionals use every day, furthering your financial management skills and success.
Keywords: Corporations,Công ty kinh doanh; Finance,Tài chính